Orthopedic manifestations and management of nail-patella syndrome: a narrative review - Beaugé, Amandine; Sbampato, Viola; Vazquez, Oscar; De Marco, Giacomo; Steiger, Christina; Dayer, Romain; Ceroni, Dimitri (Frontiers in Pediatrics, 2026)
Nail-patella syndrome (NPS) is a rare autosomal dominant disorder characterized by skeletal and renal abnormalities. Diagnosis is primarily clinical, based on four main features: nail dysplasia, patellar and elbow abnormalities, and the presence of iliac horns. NPS affects approximately 1 in 50,000 individuals. Its presentation is highly heterogeneous, even within families, which may delay recognition. Pathogenic variants have been identified in the LMX1B gene located on chromosome 9q34. Although best known for its orthopedic manifestations, NPS may also involve other systems, notably the kidneys and eyes, leading to nephropathy or glaucoma that can progress to severe morbidity. Clinical features may be apparent from birth but will evolve over the life course, thus highlighting the need for long-term monitoring. Management requires a multidisciplinary approach, with orthopedics playing a central role. Surgical decisions, particularly for lower-limb pathology, is individualized and guided by symptom burden and functional impairment. This narrative review summarizes the current literature on NPS, including its epidemiology, etiopathogenesis, clinical manifestations, and natural history. It reviews diagnostic challenges based on clinical and radiologic features. Finally, it critically appraises reported surgical management strategies, with particular emphasis on knee pathology and associated complications, with aims to guide current clinicians.